A comprehensive review of hormonal and biological therapies for endometriosis: latest developments. (3rd April 2019) - Barra, Fabio; Grandi, Giovanni; Tantari, Matteo; Scala, Carolina; Facchinetti, Fabio; Ferrero, Simone
ABSTRACT: Introduction : Endometriosis is a chronic benign estrogen-dependent disease characterized by the presence of endometriotic glands and stroma outside the uterine cavity. Although combined hormonal contraceptives and progestins, currently available first-line treatments for endometriosis, are efficacious and well tolerated for treating disease-related pain, some women experience partial or no improvement of pain or its recurrence is frequent after discontinuation of the therapies. For these reasons, new drugs are under investigation for the treatment of endometriosis. Areas covered : This review aims to give to the reader a complete and updated overview of hormonal and biological therapies for the treatment of endometriosis, underlining the latest developments in this field of research. Expert opinion : Among the new drugs investigated, late clinical trials on gonadotropin-releasing hormone (GnRH) antagonists and aromatase inhibitors (AIs) have demonstrated the most promising results. For this reason, elagolix, a new GnRH-antagonist, recently received the approval by the Food and Drug Administration (FDA) for treating pain associated to endometriosis. Other drugs with innovative targets have been identified, but the majority of these compounds have only been evaluated in pre-clinical studies or early clinical trials. Thus, a further extensive clinical research is necessary to better elucidate their pharmacologic characteristics, their efficacy, and safety for the treatment of this benign chronic disease.